Keabsahan Tanda Tangan Elektronik dalam Perspektif Hukum Positif di Indonesia - Nassya Valya Nabila; Flora Dianti; Enny Koeswarni (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The rapid development of information technology has driven digital transformation in various legal practices, including the use of electronic signatures in civil law transactions. In Indonesia, electronic signatures have been legally recognized through Law Number 11 of 2008 on Electronic Information and Transactions as amended by Law Number 19 of 2016. Nevertheless, in practice, debates continue to arise regarding the legal validity of electronic signatures, particularly in relation to civil law principles and notarial law, as well as the emergence of legal, technological, and literacy-related issues within society. This study aims to analyze the legal validity of electronic signatures from the perspective of Indonesian positive law and to examine the legal, technological, and literacy issues arising from their implementation, along with efforts to minimize such challenges. This research employs a normative legal research method using statutory and conceptual approaches by examining primary and secondary legal materials. The findings indicate that electronic signatures possess legal force and binding legal effect provided that the requirements stipulated under the Electronic Information and Transactions Law are fulfilled. However, their application is not absolute and must be harmonized with other legal provisions, particularly those governing authentic deeds. Furthermore, legal, technological, and literacy issues remain significant challenges that require regulatory harmonization, strengthened governmental supervision, and improved legal and technological literacy to ensure legal certainty in the use of electronic signatures in Indonesia.